2014
DOI: 10.1016/j.biomaterials.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophage phenotype in vascularization of tissue engineering scaffolds

Abstract: Angiogenesis is crucial for the success of most tissue engineering strategies. The natural inflammatory response is a major regulator of vascularization, through the activity of different types of macrophages and the cytokines they secrete. Macrophages exist on a spectrum of diverse phenotypes, from “classically activated” M1 to “alternatively activated” M2 macrophages. M2 macrophages, including the subsets M2a and M2c, are typically considered to promote angiogenesis and tissue regeneration, while M1 macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
767
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 787 publications
(809 citation statements)
references
References 83 publications
39
767
2
1
Order By: Relevance
“…8,9 M2a macrophages secrete the highest levels of PDGF-B, a chemoattractant stabilizing pericytes, and also promote anastomosis of sprouting endothelial cells in vitro. 10,11 Although PDGF is synthesized, stored, and released by platelets upon activation, it is also produced by a plethora of other cells, including smooth muscle cells, activated macrophages such as alveolar macrophages, and vascular endothelial cells. 12 Macrophages of M2c type express high levels of cluster of differentiation 163 (CD163), which has been shown to be associated with tissue repair and remodeling of the wound and promoting cell proliferation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 M2a macrophages secrete the highest levels of PDGF-B, a chemoattractant stabilizing pericytes, and also promote anastomosis of sprouting endothelial cells in vitro. 10,11 Although PDGF is synthesized, stored, and released by platelets upon activation, it is also produced by a plethora of other cells, including smooth muscle cells, activated macrophages such as alveolar macrophages, and vascular endothelial cells. 12 Macrophages of M2c type express high levels of cluster of differentiation 163 (CD163), which has been shown to be associated with tissue repair and remodeling of the wound and promoting cell proliferation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have demonstrated that macrophage and monocyte phenotype plays an important role in secretion of angiogenic molecules, and that their selective secretion at various time points may also be important. Spiller et al demonstrated that M1 or 'classically activated' macrophages secrete VEGF to recruit endothelial cells and initiate angiogenesis, whereas alternatively activated macrophages secrete PDGF, causing pericyte migration and vessel maintenance [19]. Our next experiments are therefore aimed at applying FACS-based approaches to elucidate the autocrine effect of PDGF-B on monocyte and macrophage phenotype at varying times during neotissue formation.…”
Section: Myeloid Cell Pdgf-b and Tevg Neotissue Development Research Armentioning
confidence: 99%
“…The in vitro polarisation of macrophages into either proinflammatory M1 or anti-inflammatory M2 that are also involved in tissue repair and angiogenesis, becomes possible via differentiation of peripheral blood monocytes utilising specific cytokines [143,144]. Importantly, it has been shown that both subsets together highly support the angiogenesis.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%